Association of liver function markers and apolipoprotein E ε4 with pathogenesis and cognitive decline in Alzheimer’s disease - Han, Sang-Won; Lee, Sang-Hwa; Kim, Jong Ho; Lee, Jae-Jun; Park, Young Ho; Kim, SangYun; Nho, Kwangsik; Sohn, Jong-Hee (Frontiers in Aging Neuroscience, 2024)
Background Alzheimer’s disease (AD) is a complex neurodegenerative disorder influenced by various factors, including liver function, which may impact the clearance of amyloid-β (Aβ) in the brain. This study aimed to explore how the apolipoprotein E (APOE) ε4 allele affects the relationship of liver function markers with AD pathology and cognition. Methods We analyzed data from two independent cohorts, including 732 participants from the Hallym University Medical Center and 483 from the Alzheimer’s Disease Neuroimaging Initiative, each group consisting of individuals with and without the APOE ε4 allele. Cross-sectional analyses evaluated the associations of liver enzymes (aspartate aminotransferase [AST], alanine aminotransferase [ALT], alkaline phosphatase, total bilirubin, and albumin) with AD diagnosis, amyloid positron emission tomography (PET) burden, and cerebrospinal fluid biomarkers for AD (Aβ42, total tau, and phosphorylated tau181) at baseline. Longitudinally, we investigated the associations between these liver enzymes and changes in cognitive performance over the course of a year. Logistic and linear regression models were used to analyze these associations and mediation analyses were conducted to assess whether age and amyloid PET burden mediated these associations. Results Only in the APOE ε4 carrier group, a high AST to ALT ratio and low ALT levels were significantly associated with AD diagnosis, increased amyloid PET burden, and faster longitudinal decline in cognitive function in both cohorts. In particular, the AST to ALT ratio was associated with cerebrospinal fluid Aβ42 levels exclusively in the APOE ε4 carrier group in the Alzheimer’s Disease Neuroimaging Initiative cohort but not with phosphorylated tau181 or total tau levels. Moreover, mediation analyses from both cohorts revealed that in the APOE ε4 carriers group, age did not mediate the associations between liver enzymes and AD diagnosis or amyloid PET burden. However, amyloid PET burden partially mediated the association between liver enzymes and AD diagnosis exclusively in the APOE ε4 carriers group. Conclusion This study provides valuable insights into the significant association of the APOE ε4 allele with liver enzymes and their potential role in Aβ-related pathogenesis and cognition in AD. Further research is required to elucidate the underlying mechanisms and potential therapeutic implications of these findings.